2021
DOI: 10.1007/s00442-021-04913-y
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid accumulation in feeding types of a natural freshwater fish population

Abstract: Fatty acids are widely used to study trophic interactions in food web assemblages. Generally, it is assumed that there is a very small modification of fatty acids from one trophic step to another, making them suitable as trophic biomarkers. However, recent literature provides evidence that many fishes possess genes encoding enzymes with a role in bioconversion, thus the capability for bioconversion might be more widespread than previously assumed. Nonetheless, empirical evidence for biosynthesis occurring in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
(103 reference statements)
0
20
0
Order By: Relevance
“…A potential explanation is that sympatric brown trout has adapted to the lower dietary intake of n-3 LC-PUFA by increasing retention and/or internal synthesis of DHA (Murray et al 2014). Such adaptation has been observed in populations of three-spined stickleback (Ishikawa et al, 2021) and European perch (Scharnweber et al, 2021) foraging on low-quality prey from littoral lake habitat that is deprived of n-3 LC-PUFA. Similarly, tree swallows have been shown to increase synthesis of DHA when consuming n-3 LC-PUFA deprived terrestrial macroinvertebrates (Twining et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…A potential explanation is that sympatric brown trout has adapted to the lower dietary intake of n-3 LC-PUFA by increasing retention and/or internal synthesis of DHA (Murray et al 2014). Such adaptation has been observed in populations of three-spined stickleback (Ishikawa et al, 2021) and European perch (Scharnweber et al, 2021) foraging on low-quality prey from littoral lake habitat that is deprived of n-3 LC-PUFA. Similarly, tree swallows have been shown to increase synthesis of DHA when consuming n-3 LC-PUFA deprived terrestrial macroinvertebrates (Twining et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…The EPA + DHA content was lower in the benthivorous perch in the eutrophic than in the mesotrophic lake. Nevertheless, DHA content alone did not differ between lakes, which is why it is possible that during the low availability of DHA in their diet, they biosynthesized DHA from ALA as was recently suggested based on the compound-specific isotope data (Scharnweber et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ahlgren et al (1996) found that EPA and DHA content of roach is higher in oligotrophic lakes than in eutrophic lakes, whereas they did not find a similar difference in the perch, which is in contrast to our previous finding with piscivorous perch (Taipale, Vuorio, et al, 2016). Chaguaceda et al (2020) recently reported that the content of ARA, EPA, and DHA are strongly regulated over ontogeny in perch muscles based on their FA profiles and compound‐specific stable isotopes (Scharnweber et al, 2021). However, it is not clear how the low availability of DHA, caused by cyanobacteria blooming driven by eutrophication or climate change, impact EPA and DHA content of fish at different trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation is that sympatric brown trout has adapted to the lower dietary intake of n-3 LC-PUFA by increasing retention and/or internal synthesis of DHA (Murray et al 2014). Such adaptation has been observed in populations of three-spined stickleback (Ishikawa et al, 2021) and European perch (Scharnweber et al, 2021) foraging on low-quality prey from littoral lake habitat that is deprived of n-3 LC-PUFA. Similarly, tree swallows have been shown to increase synthesis of DHA when consuming n-3 LC-PUFA deprived terrestrial macroinvertebrates (Twining et al, 2018).…”
Section: Discussionmentioning
confidence: 99%